Financial Savvy Unleashed: The Key Role of Knowledge, Behavior, and Access to Finance in Boosting MSME’sSuccess - Bonita, Devi Artha; Putra, Ketut Candra Pangestu; Tarigan, Rallyanta; Wati, Cicik Retno (Jurnal Manajemen Agribisnis dan Agroindustri, 2025)
The issue of Sustainable Development Goals (SDGs) has a direct impact on the increase of a country’s Gross Domestic Product (GDP), particularly in the tourism sector. The growth of Micro, Small, and Medium Enterprises (MSMEs) has become a key factor in the success of this increase. However, capital constraints remain a challenge in unlocking the potential of MSMEs. Many MSME business owners are still not bankable and lack confidence in accessing capital. The purpose of this study is to examine the relationship between financial knowledge, financial behavior, access to finance, and firm performance among MSME owners in the thematic villages of Malang City. Using an explanatory research approach, the data collected were analyzed through SEM-PLS. The findings show that financial knowledge and financial behavior havea significant effect on firm performance, while access to finance does not influence firm performance.